2005
DOI: 10.1021/jp045443u
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Chemistry of C4Hydrocarbons on Pt(111):  Mechanism for Double-Bond Isomerization

Abstract: The thermal chemistry of a number of C4 hydrocarbons (1,3-butadiene, 1-bromo-3-butene, 1-bromo-2-butene, trans-2-butene, cis-2-butene, 1-butene, 2-iodobutane, 1-iodobutane, and butane) was investigated on clean and hydrogen- and deuterium-predosed Pt(111) single-crystal surfaces by temperature-programmed desorption and reflection-absorption infrared spectroscopy. A combination of rapid beta-hydride eliminations from alkyls to olefins and the reverse insertions of those olefins into metal-hydrogen bonds explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
84
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 59 publications
11
84
3
Order By: Relevance
“…[1][2][3] This is a surprising result that runs counter to thermodynamic expectations, and not what is usually observed in alkene catalytic conversions. 4,5 It was hypothesized that the cis-trans isomerization reversal may be associated with structural details of the surface, which could therefore be used to tune selectivity in catalysis.…”
contrasting
confidence: 64%
“…[1][2][3] This is a surprising result that runs counter to thermodynamic expectations, and not what is usually observed in alkene catalytic conversions. 4,5 It was hypothesized that the cis-trans isomerization reversal may be associated with structural details of the surface, which could therefore be used to tune selectivity in catalysis.…”
contrasting
confidence: 64%
“…In another example, the dehydrogenation of cyclohexene was found to be faster on Pt (111) than on Pt (100) single-crystal surfaces (16). Our recent surface-science investigations on the isomerization of unsaturated olefins (17)(18)(19) strongly suggest that selectivity toward the formation of the cis isomer may be favored by Pt (111) facets. Additional surfacescience reports on the conversion of alkyl and alkene adsorbates under vacuum conditions (20)(21)(22)(23)(24)(25), as well as studies with more realistic model systems (26,27), point to a potential structure sensitivity in the conversion of other olefins and unsaturated hydrocarbons.…”
mentioning
confidence: 96%
“…Although the conversion of alkenes by transition metals is one of the oldest and most studied systems in catalysis (51)(52)(53), key issues such as the dependence of activity on structure remain unresolved (54). As mentioned in our Introduction, results from recent surface-science work in our laboratory have indicated that, at least on Pt (111) single-crystal surfaces, the isomerization of trans-2-butene to its cis isomer is easier than the opposite cis-totrans conversion (17)(18)(19). A kinetic study on the catalytic conversion of butenes on single-crystal surfaces (55) has also suggested different selectivities on Pt (111) vs. Pt (100) surfaces.…”
mentioning
confidence: 99%
“…Similar arguments can be made for the conversion of alcohols and for the oxidation of hydrocarbons [20]. Figure 8 displays the energy diagram of a third example, that of the migration and cis-trans isomerization of double bonds in olefins [167]. It can be seen there that the relative yields for 1-, cis-2-, and trans-2-butenes in a given catalytic process may rely on the relative rates for b-hydride elimination from different positions within the common 2-butyl surface intermediate.…”
Section: Discussionmentioning
confidence: 73%